Historical and Socio-political Perspectives of the Caribbean Region on Mental Health - Nicolas, Guerda; Wheatley, Anna (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2014)
Abstract The story of the Caribbean region includes a legacy of eradication of indigenous populations, slave labor, and colonial hegemony that has shaped the economies, social structures, and cultures of each island/nation uniquely. This paper presents a brief historical and socio-political examination of the psychological impact of histories of subordination, in an effort to contextualize the experiences of the individuals in these islands, as they pertain to effectively addressing the region’s mental health needs. The field of psychology holds promise for addressing legacies of colonialism on identity and subjectivity, particularly as an emphasis is placed on internal knowledge production. The 2011 Caribbean Regional Conference of Psychology is one such example of a movement towards unification and ownership of Caribbean Psychology perspectives, leaders, and the next generation of scholars. Abstracto La historia de la región del Caribe incluye un legado de la erradicación de las poblaciones indígenas, la escalvitud y la hegemonía colonial que ha formado la economía, las estructuras sociales y culturas de cada isla/nación. Éste artículo presenta un breve análisis histórico y sociopolítico del impacto psicológico de la historia de subordinación con el intento de contextualizar las experiencias de los individuos en estas islas, cubriendo las necesidades de salud mental de la región adecuadamente. El campo de la psicología ofrece las esperanza de enfrentar el legado de colonialismo en la identidad y la subjetividad, especialmente en la producción de conocimiento interno. La Conferencia Regional del Caribe 2011 de la Psicología es un ejemplo del movimiento hacia la unificación y la propiedad de las perspectivas de la psicología del Caribe, líderes, y la próxima generación de eruditos .